Electron Diffraction Enables the Mapping of Coke in ZSM‐5 Micropores Formed during Methanol‐to‐Hydrocarbons Conversion. (25th May 2022) - Wennmacher, Julian T. C.; Mahmoudi, Soheil; Rzepka, Przemyslaw; Sik Lee, Sung; Gruene, Tim; Paunović, Vladimir; van Bokhoven, Jeroen A.
Abstract: Unveiling the coke formation in zeolites is an essential prerequisite for tackling the deactivation of these catalysts in the transformations of hydrocarbons. Herein, we present the direct mapping of coke in the micropores of ZSM‐5 catalysts used in methanol‐to‐hydrocarbons conversion by single‐crystal electron diffraction analysis. The latter technique revealed a polycyclic aromatic structure along the straight channel, wherein the high‐quality data permit refinement of its occupancy to about 40 %. These findings were exploited to analyze the evolution of micropore coke during the reaction. Herein, coke‐associated signals, which correlate with the activity loss, indicate that the nucleation of coke commences in the intersections of sinusoidal and straight channels, while the formation of coke in the straight pores occurs in the late stages of deactivation. The findings uncover an attractive method for analyzing coke deposition in the micropore domain. Abstract : Electron diffraction was demonstrated here as a powerful tool to localize coke in the micropore domain of the ZSM‐5 catalyst that is deactivated in methanol‐to‐hydrocarbon conversion. The results show that the formation of coke is initiated in the channel intersections, while its deposition in the straight pores occurs in the late deactivation stages.